Melanocortin Peptide Therapy for the Treatment of Arthritic Pathologies - S. J. Getting; M. Kaneva; Y. Bhadresa; D. Renshaw; Giovanna Leoni; H. B. Patel; M. J. P. Kerrigan; I. C. Locke (The Scientific World Journal)
Arthritic pathologies are a major cause of morbidity within the western world, with rheumatoid arthritis affecting approximately 1% of adults. This review highlights the therapeutic potential of naturally occurring hormones and their peptides, in both arthritic models of disease and patients. The arthritides represent a group of closely related pathologies in which cytokines, joint destruction, and leukocytes play a causal role. Here we discuss the role of naturally occurring pro-opiomelanocortin (POMC)-derived melanocortin peptides (e.g., alpha melanocyte stimulating hormone [a-MSH]) and synthetic derivatives in these diseases. Melanocortins exhibit their biological efficacy by modulating proinflammatory cytokines and subsequent leukocyte extravasation. Their biological effects are mediated via seven transmembrane G-protein-coupled receptors, of which five have been cloned, identified, and termed MC1 to MC5. Adrenocorticotrophic hormone represents the parent molecule of the melanocortins; the first 13 amino acids of which (termed a-MSH) have been shown to be the most pharmacologically active region of the parent hormone. The melanocortin peptides have been shown to display potent anti-inflammatory effects in both animal models of disease and patients. The potential anti-inflammatory role for endogenous peptides in arthritic pathologies is in its infancy. The ability to inhibit leukocyte migration, release of cytokines, and induction of anti-inflammatory proteins appears to play an important role in affording protection in arthritic injury, and thus may lead to potential therapeutic targets.